Metal Impurities in Silicon- and Germanium-Based Technologies Origin, Characterization, Control, and Device Impact - Claeys, Cor (Springer Series in Materials Science,, 2018)
This book gives a unique review of different aspects of metallic contaminations in Si and Ge-based semiconductors. All important metals are discussed including their origin during crystal and/or device manufacturing, their fundamental properties, their characterization techniques and their impact on the electrical device performance. Several control and possible gettering approaches are addressed. The book is a reference for researchers and engineers studying advanced and state-of-the-art micro- and nano-electronic semiconductor devices and circuits. It has an interdisciplinary nature by combining different disciplines such as material science, defect engineering, device processing, defect and device characterization and device physics and engineering.